2016
DOI: 10.1128/iai.00469-16
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Pathogenesis: Fitting within the Host-Microbe Damage Response Framework

Abstract: f Historically, the nature and extent of host damage by a microbe were considered highly dependent on virulence attributes of the microbe. However, it has become clear that disease is a complex outcome which can arise because of pathogen-mediated damage, host-mediated damage, or both, with active participation from the host microbiota. This awareness led to the formulation of the damage response framework (DRF), a revolutionary concept that defined microbial virulence as a function of host immunity. The DRF ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
158
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(169 citation statements)
references
References 164 publications
4
158
0
7
Order By: Relevance
“…The strategies that we used to come to these conclusions (longitudinal imaging and neutrophil modulation) have not yet been applied to this question and therefore add weight to the hypothesis that neutrophil recruitment and/or activation at the site of infection controls the progression of disease. This is consistent with several studies of murine oral candidiasis but is in contrast to the findings of studies of vulvovaginal candidiasis that suggested that neutrophil recruitment is detrimental rather than protective (4). Our data also show that blockade of neutrophil recruitment results in an increased pathogen load and less damage to fungal hyphae, suggesting that neutrophils protect by damaging fungi rather than promoting disease tolerance (56).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The strategies that we used to come to these conclusions (longitudinal imaging and neutrophil modulation) have not yet been applied to this question and therefore add weight to the hypothesis that neutrophil recruitment and/or activation at the site of infection controls the progression of disease. This is consistent with several studies of murine oral candidiasis but is in contrast to the findings of studies of vulvovaginal candidiasis that suggested that neutrophil recruitment is detrimental rather than protective (4). Our data also show that blockade of neutrophil recruitment results in an increased pathogen load and less damage to fungal hyphae, suggesting that neutrophils protect by damaging fungi rather than promoting disease tolerance (56).…”
Section: Discussionsupporting
confidence: 92%
“…The opportunistic nature of C. albicans mucosal infection suggests that there is a constantly challenged impasse between our immune defenses and C. albicans virulence factors (3,4). Chronic mucocutaneous candidiasis (CMC) is associated with inborn errors of adaptive immune pathways, especially Th17 immunity (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay of colonization, host response, and damage was elegantly summarized by Casadevall and Pirofski in the "damage-response framework" (DRF), a rubric describing a pathogen's ability to cause disease on a continuum of host immune status and damage capacity (38). Recently, Jabra-Rizk and colleagues revisited the DRF in the context of C. albicans pathogenesis specifically, concluding that VVC fits into class 6 of the DRF, in which a pathogen causes damage only in the context of an aggressive immune response (39). Based on these and previous findings, this appears to hold true, given that robust PMN and cytokine levels are strongly associated with disease symptomatology and centrally dependent on the capacity of Candidalysin to cause damage.…”
Section: Figmentioning
confidence: 99%
“…Havadan izole edilen bir Aspergillus kökeni ile enfeksiyon etkeni olan bir başka Aspergillus kökeni arasın-daki virülans farkının araştırıldığı az sayıda yayın bulunmaktadır (1) . Mantarların virülans faktörleri genellikle maya mantarları ve en çok da Candida cinsi ile çalışılmıştır (5) . Hayvan modelleri ile yapılan in vivo çalışma sayısı ise daha da azdır (6) .…”
Section: Introductionunclassified